Pengaruh service quality dan reference group terhadap keputusan konsumen dalam berbelanja di Lotte Mart - Kurniawan, Ryan; Matahari, Riki (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This research is motivated by the growth rate of hypermarkets in Bandung. This of course will affect the number of people who shop in modern markets or hypermarkets. Shopping service providers must prepare the best strategy to attract consumers, because with the emergence of new outlets, consumers have more choices. Lotte Mart hypermarket is one of the outlets affected by this imbalance. It can be seen from the number of outlets between its competitors, namely Indomart. The problem in this study is "what factors influence a person's decision to choose to shop at Lotte Mart". Specifically focused on two variables, namely Service Quality and Reference Group. The purpose of this research is to be able to study the influence of these two variables in influencing consumer decisions in choosing to shop at Lotte Mart. The population in this study are Lotte Mart hypermarket consumers. The number of samples used in the study were 100 random consumers, using the accidental sampling method with a random sampling approach. Methods of data collection using a questionnaire. Data analysis used descriptive percentage analysis and multiple linear regression analysis. Based on the results of the study, it is known that there is an influence of Service Quality and Reference Group on consumer decisions. Simultaneously the effect based on the F test was obtained a value of 11.776. This study concludes that Service Quality and Reference Group have a positive and significant effect on consumer decisions in choosing to shop at Lotte Mart.